The impact on increase in fuel price on MISC Integrated Logistic Sdn Bhd (MILS) road haulage usage for the year 2004 until 2006 / Naeimatul Malmas Omar - Omar, Naeimatul Malmas (Faculty of Business and Management, 2006)
The objective of the study is to identify the impact on increase in fuel price on MISC Integrated Logistics Sdn Bhd (MILS) haulage usage for year the 2004 until 2006. The study focus on the impact either positive or negative to the haulier operator when there is increased in fuel price. The dependent variable is the number of haulage by trip/movement and independent variable is the total number by container, the diesel price and the fuel consumption. The method used to analyze are the multi linear regression. Under this the data analyzed using the Durbin-Watson Test, Coefficients of Determination (R2), Coefficient, and Hypothesis (P-Value). The result indicates that there are no significant relationships with the haulage road usage when the price of fuel increases. In the study also indicate positive relationship between the numbers of haulage road movements with the total number by containers.